2013
DOI: 10.1002/bab.1073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immobilized polygalacturonase from Mucor circinelloidesITCC‐6025 on wine fermentation

Abstract: Pectinases are among the most widely distributed enzymes in bacteria, fungi, and plants. Almost all the commercial preparations of pectinases are produced from fungal sources. Mucor circinelloides ITCC-6025 produced polygalacturonase when grown in Riviere's medium containing pectin (methyl ester) as the sole source of carbon. Immobilization of purified polygalacturonase was done on silica gel with 86% efficiency. The enzyme took 60 Min to bind maximally on the support. The immobilized enzyme showed maximum act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…fulva after 30 days of fermentation. In a previous study, Sharma et al (2013) reported that the use of pectinase from Mucor circinelloides in apple wine fermentation showed decrease in the amount of carbohydrates from 102 to 61 μg/mL and increase in the amount of phenolics from 0.29 to 0.48 mg/ mL. In a similar study, Sharma et al (2013) reported that pectinase from M. circinelloides used in apple wine fermentation showed ethanol level increased from 10.02 to 14.2% v/v and 4.62 to 6.09% v/v in case of plum wine fermentation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…fulva after 30 days of fermentation. In a previous study, Sharma et al (2013) reported that the use of pectinase from Mucor circinelloides in apple wine fermentation showed decrease in the amount of carbohydrates from 102 to 61 μg/mL and increase in the amount of phenolics from 0.29 to 0.48 mg/ mL. In a similar study, Sharma et al (2013) reported that pectinase from M. circinelloides used in apple wine fermentation showed ethanol level increased from 10.02 to 14.2% v/v and 4.62 to 6.09% v/v in case of plum wine fermentation.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, Sharma et al (2013) reported that the use of pectinase from Mucor circinelloides in apple wine fermentation showed decrease in the amount of carbohydrates from 102 to 61 μg/mL and increase in the amount of phenolics from 0.29 to 0.48 mg/ mL. In a similar study, Sharma et al (2013) reported that pectinase from M. circinelloides used in apple wine fermentation showed ethanol level increased from 10.02 to 14.2% v/v and 4.62 to 6.09% v/v in case of plum wine fermentation. Stepanova et al (2006) also found decrease in the contents of the carbohydrates and increase in the amount of phenolics in case of cherry plum wine, while using immobilized preparations of different commercially available polygalacturonases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation